Dowody legalizacji przyrządów pomiarowych jako prawne formy działania administracji gospodarczej (administracji miar) - Żywicka, Agnieszka; Bieś-Srokosz, Paulina (PRAWO i WIĘŹ, 2025)
The study analyses the regulations governing legal metrological control to determine the legal nature of legalisation certificates and the legalisation of measuring instruments, with the aim of classifying these activities as forms of economic administration. These determinations are significant because assigning these activities to specific legal forms determines the scope of judicial control of the administration of measures performed by administrative courts, as well as the means of control (administrative sanctions) applied in the event of a legal violation. The paper proves the thesis that the certificate of legalisation and the process of legalisation are authoritative forms of economic administration activity – specifically, the administration of measures – and can be considered specific individual administrative acts.